Spectrum of Colonoscopy in Children: A Tertiary Centre Experience from Bangladesh - Mahmud, Salahuddin; Parvez, Mashud; Baidya, Madhabi; Rashid, Rafia; Tasneem, Farhana; Hasan, Ahmed Rashidul; Farhana, Tanzila; Asha, Nafis Fatema; Alam, Jahangir; Ahmed, Syed Shafi (Dhaka Shishu (Children) Hospital Journal, 2023)
Background: Pediatric colonoscopy is a safe, sensitive and crucial tool for diagnosing as well as treating children with lower gastrointestinal diseases. In resource-limited countries like Bangladesh, the practice of pediatric colonoscopy remains rudimentary, lacking in trained professionals and appropriate instrumentation. Objectives: The aim of the study was to find out the indications, common colonoscopic findings along with histopathologic evaluation and immediate post procedure complications of colonoscopy in children. Methods: This was a retrospective study; the records of all the patients whose age was less than 18 years and who underwent colonoscopy from January 2017 to December 2021 were studied. Results: Among the total of 196 children (8.23±4.12), the most common indications were lower gastrointestinal bleeding (LGIB) in 107 (54.6%) patients followed by chronic diarrhea in 33 (16.8%), recurrent abdominal pain (RAP) in 16 (8.2%), follow up Inflammatory bowel diseases (IBD) in 14 (7.1%), chronic constipation, weight loss, recurrent oral ulcer, intestinal tuberculosis (TB) and melena. The most common pathologic findings were polyps in 81 (61.4%) children followed by non-specific colitis in 19 (14.4%), IBD in 17 (12.9%) and infectious colitis in 09 (6.8%) cases. Minor adverse events occurred in only 2.0% of children. Conclusion: The commonest indication for pediatric colonoscopy was LGIB and the most common findings were colonic polyps. Pediatric colonoscopy is safe and effective diagnostic as well as therapeutic option for lower GI diseases. DS (Child) H J 2021; 38(1): 8-16